Pemberdayaan Ekonomi Berbasis Ekonomi Sirkular Melalui Pemanfaatan Lidi Sawit di Kampung Benit - Novita Eka Paradina; Reti Suryani; Nayla Wulandani; Soedimas Wahyudi (khidmatan, 2026)
This study aims to comprehensively analyze the community economic empowerment program through the optimization of oil palm frond midrib (lidi sawit) waste in Kampung Benit, Sungai Mengkuang Village, Bungo Regency. Adopting the Asset-Based Community Development (ABCD) framework, this action-oriented initiative maps and mobilizes local assets to transition rural livelihoods from illegal, environmentally destructive gold mining activities toward a legal, green creative economy. Data were gathered through structured in-depth interviews, participatory observations, and extensive documentation of 30 active participants representing the local Family Welfare Movement (PKK) and Women Farmers Group (KWT). The findings indicate that the implementation of structured technical training encompassing material selection, chemical preservation, advanced weaving techniques for party plates, and decorative gloss finishing significantly enhanced the artisans' motor skills and production capacities. In addition to technical mastery, the program provided intensive mentoring to secure formal business permits, specifically obtaining Business Identification Numbers (NIB) through the OSS-RBA platform and free halal certification (SEHATI). The diversification of household income from this eco-friendly handicraft enterprise has successfully bolstered family financial stability, mitigated ecological degradation caused by illegal mining, and fostered sustainable social resilience within the rural community.